The Problem of Easelism in Russian Lacquer Crafts of the Soviet Period - Lavrov, Dmitrii E. (Actual Problems of Theory and History of Art, 2022)
The article considers the problem of easelism, one of the key ones for the Soviet art studies of Russian lacquer crafts of the 20th century. The debate about the possibilities of developing the art of Palekh, Mstiora, Kholui, and Fedoskino along the path of imitating the easel picture, which started in the early 1930s as a response to the already established practice of miniature painters, turned out to be extremely long and fierce, surviving to the very end of the Soviet period. The article gives the arguments of the Soviet art historians “for” and “against” easelism in Russian lacquer miniature, analyzes the attitude of the miniature painters themselves to such a manual, and considers their works made in a similar “easel” style. In conclusion, the article discusses the practical outcome of the development of Russian lacquered miniature, which manifested itself as a response to such discussions during Soviet and Post-perestroika periods. The author concludes that the trends of easelism in Russian lacquer crafts, being an objective result of the relationship between miniature artists and “urban” culture, despite the declarative rejection proclaimed in the 1950s, persist until the end of the Soviet period, having a heyday already in the modern post-perestroika period.
Keywords: Palekh; Mstiora; Kholui; Fedoskino; lacquer miniature; Soviet art history